7-( 3 + x - 1 )= -1 , x = ...
Răspunsuri la întrebare
Răspuns de
2
7-( 3 + x - 1 )= -1
Notam ( 3 + x - 1 ) cu Y
7-Y= -1
Y=-7-(-1)
Y=7+1
Y=8 dar
Y=( 3 + x - 1 )
3+x-1=8
3+x= 8+1
3+x=9
x=9-3
x=6
Notam ( 3 + x - 1 ) cu Y
7-Y= -1
Y=-7-(-1)
Y=7+1
Y=8 dar
Y=( 3 + x - 1 )
3+x-1=8
3+x= 8+1
3+x=9
x=9-3
x=6
Răspuns de
1
7-( 3 + x - 1 )= -1
-(3+x-1)=-1-7
-(3+x-1)=-8 Ix (-1)
3+x-1=8
x=8-3+1
x=6
-(3+x-1)=-1-7
-(3+x-1)=-8 Ix (-1)
3+x-1=8
x=8-3+1
x=6
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Studii sociale,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă